Clicked Cinnamic/Caffeic Esters and Amides as Radical Scavengers and 5-Lipoxygenase Inhibitors. (18th February 2014) - Doiron, Jérémie A.; Métayer, Benoît; Richard, Ryan R.; Desjardins, Dany; Boudreau, Luc H.; Levesque, Natalie A.; Jean-François, Jacques; Poirier, Samuel J.; Surette, Marc E.; Touaibia, Mohamed
Abstract : 5-Lipoxygenase (5-LO) is the key enzyme responsible for the conversion of arachidonic acid to leukotrienes, a class of lipid mediators implicated in inflammatory disorders. In this paper, we describe the design, synthesis, and preliminary activity studies of novel clicked caffeic esters and amides as radical scavengers and 5-LO inhibitors. From known 5-LO inhibitor3 as a lead, cinnamic esters8a–h and amides9a–h as well as caffeic esters15a–h and amides16a–h were synthesized by Cu(I)-catalyzed [1, 3]-dipolar cycloaddition with the appropriate azide precursors and terminal alkynes. All caffeic analogs are proved to be good radical scavengers (IC50 : 10–20 μ M). Esters15g and15f possessed excellent 5-LO inhibition activity in HEK293 cells and were equipotent with the known 5-LO inhibitor CAPE and more potent than Zileuton. Several synthesized esters possess activities rivaling Zileuton in stimulated human polymorphonuclear leukocytes.